The Application of Learning Based on Local Wisdom at SMA Negeri 1 Medan as an Effort to Development the Character of an Inclusive Nation - Amin, Muryanto; Ritonga, Alwi Dahlan (Talenta Publisher, 2022)
This activity aims to help the world of education, in this case SMAN 1 Medan to overcome the threat of radicalism and the degradation of the national character of school children. The method used in this service is in the form of socialization and Participatory Learning and Action (PLA). The learning module for improving national character consists of 4 main topics, namely: (1) National Insights Module (2) Multiculturalism Module (3) Local Wisdom Module (3) Radicalism Module. These four modules will be taught to SMA Negeri 1 Medan students. This school is located in the city center, a pilot school in government programs at various levels. The target to be achieved through this service is to increase quality education by the standing of the success of the world's SDGs. In addition, there is also an increased sense of state defense and national insight that creates a national character who cares about the values of Pancasila in practice in everyday life.